Hans Jonas : fundamentos éticos do princípio resposabilidade - Balbinot, Eliana Silvia (My University, 2015)
A research about the Responsability Principle proposed by Hans Jonas is the subject of the present paper. Explaining about the singularities of responsibility under the philosophical perspective that embraces a new ethical action towards the technological moment is one of its aims. The justification for the choice of this topic is on the necessity of expanding the reflection about human action in relation to nature, since it has not been following the environmental problematics of contemporary world. The philosophical question that permeates this dissertation is as follows: what are the main bases of ethics that constitute the Responsibility Principle? The central and secondary objectives are useful for understanding the ethical aspects intrinsic in the Responsibility Principle proposed by Hans Jonas and for the research about the characteristics of responsibility, as autonomy, reasoning and freedom respectively. Methodologically, for being a theoretical study, a descriptive research including a bibliographical research was used. The research is also characterized by the expositive typology, since it gathers complementary sources for the data resurgence and organization. The Principle of Responsibility can be understood as a concept that is closely related to the virtue and the sense of universal responsibility. Furthermore, it is a driving force based on an ethic of relations of humans with the environment, each having a role. Both of them are interrelated and as a new imperative for the entire human kind, taking into account that the continuous progress cannot be stopped.
Uma pesquisa sobre o Princípio Responsabilidade proposto por Hans Jonas é o assunto do presente trabalho. Buscou-se explicitar sobre as peculiaridades da responsabilidade sob uma perspectiva filosófica englobando um novo agir ético frente ao momento tecnológico. A justificativa para a escolha deste tema está na necessidade de ampliação da reflexão sobre o agir humano em relação a natureza, uma vez que este não tem acompanhado a problemática ambiental da atualidade. A questão filosófica que permeia esta dissertação ficou assim descrita: quais os principais fundamentos da ética constituem o Princípio Responsabilidade? Os objetivos centrais e secundários buscam realizar uma pesquisa para compreender os aspectos da ética inseridos no Princípio Responsabilidade propostos por Hans Jonas e pesquisar sobre as características da responsabilidade, sendo estas, autonomia, razão e liberdade respectivamente. Metodologicamente, por se tratar de um estudo teórico, utilizou-se pesquisa bibliográfica. Caracteriza-se também pela tipologia expositiva uma vez que reúne fontes complementares e de apoio para o levantamento e organização dos dados. Pode-se compreender o princípio da responsabilidade como um conceito que está estreitamente ligado à virtude e ao senso de responsabilidade universal. Ademais, é uma força motriz fundamentada em uma ética das relações do homem com o meio ambiente, onde, cada um tem um papel e todos estão interligados.
Keywords: Jonas, Hans, 1903-1993; Responsabilidade; Ética; Autonomia (Filosofia); Responsibility; Ethics; Autonomy (Philosophy)